The factors affecting Vietnam's canned tuna exports - Nguyen Hong Nga; Le Thi Xoan (Cogent Economics & Finance, 2024)
In this study, we used the gravity model to identify factors affecting Vietnam's tuna exports to major import markets, including the United States, Canada, Japan and European countries, and then to find the solutions with sufficient scientific and practical basis to promote the development of the tuna export industry in the future. This research'results show that an increase in factors including domestic tuna production, exchange rates, population of the importing country and geographical distance leads to increase the scale of Vietnam' tuna exports, with the exchange rate playing the most important role, while the import tax rate is the significant barrier that reduces Vietnam's tuna exports. In order to develop the tuna export sustainably in the future, Vietnam must maintain tight control over the domestic tuna resources, avoid overexploitation, and instead focus on enhancing product quality. Furthermore, it is critical to focus on satisfying the conditions of commitments in signed free trade agreements, actively analyzing the market and paying attention to trade promotion policies, growing trade connections with importing countries.
Keywords: 330; factors affecting to exports; Tuna; Vietnam